A Novel Power Flow Algorithm for Hybrid AC/DC Power Grids. Issue 14 (27th August 2017) - Zhang, Xinyi; Han, Xueshan; Yang, Ming; Sun, Donglei; Zhang, Yumin; Gai, Wuyang
Abstract: This study introduces a novel unified power flow algorithm for hybrid AC/DC power grids. For hybrid AC/DC power grids that incorporate voltage source converters (VSCs), the proposed algorithm uses the voltage amplitude and the phase angle of the AC bus and the voltage of the DC bus as the minimum set of state variables. The power equation of the converter is deduced by these state variables. Then, the bus-power-equilibrium (BPE) equations can be deduced based on the DC node classification and VSC converter station control modes. The Newton–Raphson method can be used to solve these BPE equations with good convergence behavior. In addition, the DC grid and converter station modeling impose no restriction on the hybrid grid topology. As a result, the Jacobian matrix in the modified equations can accurately reflect the coupling relationship between AC and DC grids and simultaneously maintain the sparse feature. The proposed unified algorithm uses the sparse technology and can solve the power flow problem for a large hybrid power grid. A simulation is implemented to illustrate the effectiveness of the proposed algorithm.